Literacy and Numeracy Research Trends for Elementary School Student: A Systematic Literature Review - M Zainudin; Doni Abdul Fatah; Junarti Junarti (STKIP Singkawang, 2023)
Literation and numeracy are among the basic skills needed by primary school-aged children to develop 21st-century skills. This triggered massive innovations in educational research related to literacy and numeracy. This content analysis study aimed to systematically analyze the trends of literacy and numeracy research of elementary school students based on articles published in national and international journals. Based on the established inclusion criteria, 20 articles were collected for analysis using the Paper Classification Form (PCF) instrument. The results of the analysis showed the dominance of the topic of literacy and numeracy implementation (45%) themed on daily activities (41.67%) with the case study method (35%). The most common integration pattern found was contextual learning (38.46%). Interest (58.33%) and problem-solving (16.67%) were the dominant variables associated with implementing literacy and numeracy in primary school students. Therefore, it is necessary to conduct various literacy and numeracy studies of elementary school students on other potential issues to help the government achieve national education goals.